Habitação e cidade – espaços coletivos na Habitação de Interesse Social: análise das obras do arquiteto Hector Vigliecca em São Paulo de 1989 a 2016 - Puglisi, Mariana de Carvalho (2017)
This dissertation seeks to analyze the collective spaces in three sets of social interest housing projects designed by the architect Hector Vigliecca in the city of São Paulo from 1989 to 2016. The main axis in which the research is oriented is the reality not foreseen in the Projects that arise in the appropriations of collective spaces, where they show contradictions between the architecture project commissioned by the public power and the use by the residents. Throughout the research the land issue and the origin of the land appears as one of the indications of the revealed contradictions, as for example, the imprecision of land is reproduced in the uses and appropriations of the inhabitants. The work analyzes the collective spaces of each housing group chosen according to criteria for identifying characteristics that support the urban quality of the projects. The sets chosen are: Conjunto Habitacional Rincão 1989-1992, Rio das Pedras - Vila Mara 1989-1998 and Parque Novo Santo Amaro V 2009-2012. From this analysis divided into three moments the dissertation aims to address the problem of public space in housing of social interest, its relevance to the works of HIS in the construction of the city and the contradictions that exist in these spaces in the architecture project.